The optimal production-transportation problem of Latex Foam Ghana Ltd. - Krah, Collins Kwadwo (2012)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fufillment of the requirement for the degree of M.Phil Applied Mathematics